1999
DOI: 10.1094/phyto.1999.89.4.308
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenetic Analyses of Biological Control Strains of Trichoderma harzianum and Other Biotypes of Trichoderma spp. Associated with Mushroom Green Mold

Abstract: A polymerase chain reaction-amplified DNA containing the internal transcribed spacer (ITS)-1, 5.8S, and ITS-2 regions of the nuclear ribosomal DNA transcriptional unit was sequenced for 81 isolates of Trichoderma spp. associated with mushroom culture or used for biological control of plant pathogens. Phylogenetic analyses revealed that the biocontrol isolates were more closely related to an isolate of T. harzianum biotype 1 (Th1) than to the aggressive biotypes 2 and 4. Th1 has been isolated from mushroom comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 17 publications
1
22
1
2
Order By: Relevance
“…Molecular studies have confirmed the distribution of T. harzianum in the same four Seaby's biotypes, of which Th1 and Th3 seem to be nonpathogenic to mushrooms (28). Phylogenetic analysis based on ITS sequences (27) has revealed that Th1 is the most recent ancestor for aggressive mushroom colonizers which were included in Th2 (26) and Th4 (28) of T. harzianum. Th3 is coincident with T. atroviride Karsten, a previously described species with similarities in colony character to T. harzianum (21).…”
mentioning
confidence: 69%
“…Molecular studies have confirmed the distribution of T. harzianum in the same four Seaby's biotypes, of which Th1 and Th3 seem to be nonpathogenic to mushrooms (28). Phylogenetic analysis based on ITS sequences (27) has revealed that Th1 is the most recent ancestor for aggressive mushroom colonizers which were included in Th2 (26) and Th4 (28) of T. harzianum. Th3 is coincident with T. atroviride Karsten, a previously described species with similarities in colony character to T. harzianum (21).…”
mentioning
confidence: 69%
“…Trichoderma harzianum isolate (Jn14) was identified based on RAPD analysis and the sequence of (ITS) [18], and formulated as wettable powder (WP) on Talc. The isolate was grown on 90 mm PDA medium plates for 10 days.…”
Section: Trichoderma Harzianum Formulamentioning
confidence: 99%
“…Analisis sekuens internal transcribed spacer region 1 dan 2 (ITS1 dan ITS2) pada DNA ribosomal dapat membantu untuk deskripsi dan karakterisasi spesies pada genus Trichoderma (Ospina-Giraldo et al, 1999;Jeewon et al, 2013). Seluruh analisis tersebut menggunakan amplifikasi PCR karena dapat menghasilkan produk yang akurat, sehingga dapat digunakan dalam melakukan diagnosis (McPherson & Moller, 2006 (Regina et al, 2003).…”
Section: Pendahuluanunclassified